Jødeforfølgelse med socialistisk fortegn. Janina Katz’ forfatterskab mellem Polen og Danmark med særligt henblik på romanen Putska - Wolgast, Karin (Folia Scandinavica Posnaniensia, 2019)
Introducing life and work of Janina Katz, the article undertakes an analysis and interpretation of her second novel, the autofictional Putska. Born on the second of March 1939, Katz belonged to a renowned Jewish family with numerous members, of whom, however, only her mother and she survived the Second World War. Their extraordinary family history may be traced in practically all of Katz’ writings, as can her Jewish cultural heritage. The novel Putska is no exception. Its composition, characters and the image it gives of life in Cracow are examined in order to make understandable the protagonist’s decision to exile herself from Poland and migrate to Denmark, much like the author herself. 1969, having fled from that revival of anti-Semite harassment which was launched by the political leadership of socialist Poland, Katz was granted asylum in Denmark, where she soon learned the language to a perfection which enabled her to unfold a widely acknowledged literary work which does not cease to speak of her unique life experience. Central perspectives on her life and work include migration, autobiography, Jewishness and social and cultural history of Poland.